Cash flow management utilization by Small Medium Enterprises (SMEs) in Northern Uganda - Uwonda, Gilbert; Okello, Nelson; Okello, Nicholas G. (Merit Research Journal of Accounting, Auditing, Economics and Finance, 2013)
In Uganda, SMEs are considered as seedbeds for the growth of new firms and important machineries for poverty reduction through wealth and job creation, income generation as well as drivers for innovation. Cash flow management has been sighted as a nucleus of any business entity for short and long-term survival. Failures in many SMEs have been linked to inadequate cash flow management, which compromises their sustainability by denying them the revenue stream needed to grow. This study sought to establish the extent to which SMEs utilize cash flow management, which is an important factor that influences financial performance of a number of service sectors of SMEs. The research adapted a cross sectional exploratory study. Data from a sample of 120-service sector SMEs were collected and analyzed. The study highlighted limitations in utilization of cash flow in SMEs especially in areas like cash flow projection; tax planning; and budgetary control; determination and interpreting financial statements. Further, utilization of redundant fixed assets, inability to offer cash and early discounts, failure to prepare bank reconciliation and poor credit policies were other concerns for SMEs. For SMEs to reach their potentials, they must design business plan, prepare cash flow projections and cash budgeting; ensure budgetary control, internal control system and control their spending habits; and improve on their credit policies.